Midterm outcomes of arteriovenous fistula aneurysm repair with simultaneous inflow revision or outflow tract revascularization - Benfor, Bright; Singh, Tarundeep; Puppala, Rishik; Peden, Eric K. (Journal of vascular surgery, 2024)
The aim of this study was to investigate the 2-year outcomes of extensive revisions aimed at simultaneously addressing arteriovenous fistula (AVF) aneurysms, outflow stenosis, and/or high flow volumes. This was a retrospective cohort study in a tertiary referral center. The study population comprised hemodialysis patients with aneurysmal AVFs requiring revision. Subjects were eligible if they were ≥18 years of age and had aneurysm repair associated with inflow revision or treatment of outflow lesions. Patients were followed-up for a minimum of 2 years, and the primary outcome measure was cumulative patency. Our cohort comprised 93 patients with a mean age of 56 ± 12 years. The most frequent access type was brachiocephalic fistula (61%), and the median access age at the time of revision was 66 months (interquartile range, 46-93 months). The median access flow volume was 2300 ml/min (interquartile range, 1281-2900), and 31 subjects (33%) presented aneurysms associated with both high flow and venous obstruction. Aneurysm repair consisted of aneurysmorraphy in the overwhelming majority (95%). Inflow revision was performed in a total of 49 cases (53%), and outflow tract obstruction was treated in 71 patients (72%), with 27 patients (29%) receiving a simultaneous 3-component revision. At 2 years, the primary, primary assisted, and cumulative patencies were 60% ± 1%, 91% ± 3%, and 94% ± 3%, respectively. The most frequent indication for first-time reinterventions was outflow tract stenosis (24%). Aneurysm recurrence was observed in 13 subjects (14%) during the entire follow-up and was responsible for reinterventions in seven of them (8%), with a 2-year freedom from aneurysm-related reintervention rate of 95% ± 3%. Extensive AVF revision with simultaneous aneurysm repair, inflow revision, and outflow tract revascularization is feasible, safe, and associated with favorable 2-year patency rates.